Characterization and evolutionary analysis of tributyltin‐binding protein and pufferfish saxitoxin and tetrodotoxin‐binding protein genes in toxic and nontoxic pufferfishes. (12th May 2015) - Hashiguchi, Y.; Lee, J. M.; Shiraishi, M.; Komatsu, S.; Miki, S.; Shimasaki, Y.; Mochioka, N.; Kusakabe, T.; Oshima, Y.
Abstract Understanding the evolutionary mechanisms of toxin accumulation in pufferfishes has been long‐standing problem in toxicology and evolutionary biology. Pufferfish saxitoxin and tetrodotoxin‐binding protein (PSTBP) is involved in the transport and accumulation of tetrodotoxin and is one of the most intriguing proteins related to the toxicity of pufferfishes. PSTBPs are fusion proteins consisting of two tandem repeated tributyltin‐binding protein type 2 (TBT‐bp2) domains. In this study, we examined the evolutionary dynamics of TBT‐bp2 and PSTBP genes to understand the evolution of toxin accumulation in pufferfishes. Database searches and/or PCR‐based cDNA cloning in nine pufferfish species (6 toxic and 3 nontoxic) revealed that all species possessed one or more TBT‐bp2 genes, but PSTBP genes were found only in 5 toxic species belonging to genus Takifugu. These toxic Takifugu species possessed two or three copies of PSTBP genes. Phylogenetic analysis of TBT‐bp2 and PSTBP genes suggested that PSTBPs evolved in the common ancestor of Takifugu species by repeated duplications and fusions of TBT‐bp2 genes. In addition, a detailed comparison of Takifugu TBT‐bp2 and PSTBP gene sequences detected a signature of positive selection under the pressure of gene conversion. The complicated evolutionary dynamics of TBT‐bp2 and PSTBP genes may reflect the diversity of toxicity in pufferfishes.